Lipid nanostructures for targeting brain cancer. Issue 9 (September 2021) - Nsairat, Hamdi; Khater, Dima; Odeh, Fadwa; Al-Adaileh, Fedaa; Al-Taher, Suma; Jaber, Areej M.; Alshaer, Walhan; Al Bawab, Abeer; Mubarak, Mohammad S.
Abstract: Advancements in both material science and bionanotechnology are transforming the health care sector. To this end, nanoparticles are increasingly used to improve diagnosis, monitoring, and therapy. Huge research is being carried out to improve the design, efficiency, and performance of these nanoparticles. Nanoparticles are also considered as a major area of research and development to meet the essential requirements for use in nanomedicine where safety, compatibility, biodegradability, biodistribution, stability, and effectiveness are requirements towards the desired application. In this regard, lipids have been used in pharmaceuticals and medical formulations for a long time. The present work focuses on the use of lipid nanostructures to combat brain tumors. In addition, this review summarizes the literature pertaining to solid lipid nanoparticles (SLN) and nanostructured lipid carriers (LNC), methods of preparation and characterization, developments achieved to overcome blood brain barrier (BBB), and modifications used to increase their effectiveness. Abstract : Lipid nanoparticles; Blood brain barrier (BBB); Solid lipid nanoparticles (SLN); Lipid nanocarriers (LNC); Glioblastoma